Renewable Energy as a Catalyst for Equity? Integrating Inuit Interests With Nunavik Energy Planning - Paquet, Antoine; Cloutier, Geneviève; Blais, Myriam (Cogitatio Press, 2021)
Nunavik’s residents experience significant social and environmental disruptions due to climate change. These disruptions add to the widespread changes that the Inuit have encountered over the last century—changes that have left this community totally dependent on fossil fuels for heat and power. Over time, Nunavik’s residents have taken control of petroleum resources and their distribution, transforming this energy source into a major regional economic asset. Recently, there has been a transition towards renewable energy technologies (RETs) in Nunavik. However, are these alternative sources of energy appealing to local residents? This article explores the potential of RETs through the lens of procedural and substantive equity in the context of Inuit interests and integrated sustainability. Based on informal discussions with Inuit residents, interviews with stakeholders of the energy transition in Nunavik, and a literature analysis, this article presents two main results: (1) The level of substantive equity depends mainly on the type of RET and on idiosyncrasies between communities, and (2) local governance and procedural equity need to be asserted so that RETs can become true catalysts for equity.